Pengembangan Modul Teknik Dasar Pencak Silat Berbantuan Quick Responce Code di SMA Negeri Selangit - Suandi, D; Mulyono, D; Darsi, H (Educative Sportive, 2021)
This research aims to develop a basic technique module of pencak silat assisted by Quick Responce Code at SMA Negeri Selangit. The research method used was research and development. Data collection techniques using interviews, observation, and questionnaires. The data analysis technique used the steps of the validity analysis of the media expert to get a value of 85,19%, linguists get a value of 75%, and material expert to get a value of 79,76%. Furthermore, the data analysis of the practicality questionnaire of the one to one test students got a value of 80,56% and the small groups test got a value of 81,39%. From the overall results of the assessment from the one to one test and small groups test, the criteria are very practical with a value of 81,11%.